1991
DOI: 10.1115/1.2910586
|View full text |Cite
|
Sign up to set email alerts
|

Film Condensation of R-113 on In-Line Bundles of Horizontal Finned Tubes

Abstract: Film condensation of R-113 on in-line bundles of horizontal finned tubes with vertical vapor downflow was experimentally investigated. Two tubes with flat-sided annular fins and four tubes with three-dimensional fins were tested. The test sections were 3×15 tube bundles with and without two rows of inundation tubes at the top. Heat transfer measurements were carried out on a row-by-row basis. The heat transfer enhancement due to vapor shear was much less for a finned tube bundle than for a smooth tube bundle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…For the three test fluids, the jet-sheet mode began at KZ0.32, and a complete sheet was observed when K reached from 0.37 to 0.47. In a similar report for R-113 on finned tubes, Honda et al [53] found a significant increase in Re for transition from the jet mode to the sheet mode with a downward-flowing vapor. However, for three-dimensional fins this effect was dramatically reduced due to the promotion of the liquid distribution by the surface structure.…”
Section: Flow Patterns Studiesmentioning
confidence: 86%
“…For the three test fluids, the jet-sheet mode began at KZ0.32, and a complete sheet was observed when K reached from 0.37 to 0.47. In a similar report for R-113 on finned tubes, Honda et al [53] found a significant increase in Re for transition from the jet mode to the sheet mode with a downward-flowing vapor. However, for three-dimensional fins this effect was dramatically reduced due to the promotion of the liquid distribution by the surface structure.…”
Section: Flow Patterns Studiesmentioning
confidence: 86%
“…A number of researchers [10 -15] have studied the performance of the Beatty and Katz model. However, [12,14,15] have observed that the model overpredicts or underpredicts the heat transfer performance depending on the fluid and geometry of fins. Errors increase at higher fin density and for fluids having higher surface tension.…”
Section: Heat Balance Relationsmentioning
confidence: 95%
“…In experiments, either the heat transfer was measured using single tubes [25, 26, 31-34, 36, 37, 42, 43, 46, 51, 54, 55, 57, 58] and tube bundles [12,20,22,28,45,[47][48][49][50]56], or capillary phenomena and condensate retention in the lower bottom tube region [31][32][33][34]37] were analysed. As was to be expected, flooding of the lower tube portion is influenced by fin geometry and physical properties of condensate.…”
Section: Current Publicationsmentioning
confidence: 99%